State of the world's refugees (1997-98) : humanitarian agenda (Oxford, 1997)
During the last few years millions of people have been forced to abandon their homes, fleeing from communal violence, political persecution, and other human rights abuses. In a disturbing number of situations, mass expulsions and population relocations have been explicitly used by states and other actors as a means of exerting political and territorial control. Whilst the plight of uprooted populations continues to be a matter of pressing humanitarian concern, the problem of forced displacement has also assumed a much broader political significance. Refugee movements are undoubtably a symptom of the injustices and inequities which afflict our world. But they also have an increasingly significant impact on the search for regional and global security. This invaluable book from UNHCR analyses the international community's evolving response to the problem of forced displacement, focusing on issues such as the rights of asylum seekers, the protection of refugees and internally displaced people, the challenge of repatriation and reintegration, and the reduction of statelessness. In addition to providing a comprehensive examination of these crucially important humanitarian issues, the report presents a wide range of case studies, maps, statistics, and other reference material, describing the state of the world's uprooted people and the world's response to their plight. Essential reading for decision-makers, journalists, aid agency personnel, as well as scholars and students, The State of the World's Refugees 1997 provides the definitive, detailed, and up-to-date analysis of the plight of the world's many millions of displaced people.
Keywords: Human security